Граматикалізація: комунікативні стратегії та мотивації - Булатецька, Людмила Іванівна; Bulatetska, L. I. (Волинський національний університет імені Лесі Українки, 2012)
У статті розглядається явище граматикалізації на рівні а) морфофонології, б) морфології, в) синтаксису. Обґрунтовуються граматичні та прагматичні причини цього явища з позиції діахронії (морфофонологічні) та синхронії (морфологічні та синтаксичні). В результаті граматикалізації відбувається: стирання меж між граматично канонізованими та граматикалізованими значеннями; розрізняється позитивна та негативна (або нейтральна) епістемічна позиція; перехід одиниці із закритої системи у відкриту; ідентифікується однонаправленість граматикалізації на всіх рівнях аналізу мовних одиниць. The article is devoted to the phenomenon of grammaticalization at the a) morphophonological, b) morphological and c) syntactical levels. The grammatical and pragmatic reasons of this phenomenon are grounded from the diachrony (morphophonology) and synchrony (morphology and syntax). The result of grammaticalization brings to: a) obliteration the boundary between grammatically canonical and grammaticalized meanings; b) differentiation of positive and negative (or neutral) epistemic stance; c) transition of the unit from the closed to the open system; d) the unidirectionality of grammaticalization is identified at all levels of the language units analysis. The result of grammaticalization brings to: a) obliteration the boundary between grammatically canonical and grammaticalized meanings; b) differentiation of positive and negative (or neutral) epistemic stance; c) transition of the unit from the closed to the open system; d) the unidirectionality of grammaticalization is identified at all levels of the language units analysis.
Grammaticalization: communicative strategies and motivations
Keywords: граматикалізація; grammaticalization; функціональна переорієнтація; спеціалізація; виділення / затінення; конвенції; епістемічність; модифікація флексій; канонічний; functional re-orientation; specialization; conventions; epistemology; flexion modification; canonical; foregrounding / backgrounding